Cholera Control in 2021 (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cholera remains a global threat in the 21st century, chiefly due to the continued lack of adequate resource provision and the political will to ensure a safe potable water supply and sanitary waste disposal for a burgeoning global population. The current Special Issue on cholera provides an overview of the available control measures from the perspectives of bioecology, immunology and vaccinology and treatment. These modalities have the potential to reduce cholera case fatality rates to less than 1% if properly implemented. In this Special Issue on cholera, the current state of the art in science-based control measures is reported on by several of the world’s leaders in research on the control of cholera and allied acute watery diarrheal diseases. Dr. Rita Colwell, Dr. Anwar Huq and colleagues at the University of Maryland and the University of Florida will review the latest information on environmental factors related to the prediction and prevention of cholera. Dr. Jacqueline Dean and Dr. John Clemens contribute an overview of recent insights into the performance of licensed and recommended cholera vaccines. Dr. Jan Holmgren will present an update on cholera immunity and the next generation of cholera vaccines. Dr. David Nalin will discuss cholera treatment options and optimums for the 21st century, and Dr. Richard A. Cash will focus on bringing diarrhea treatment, control, and prevention to the community.